Apelin-13 facilitates lordosis behavior following infusions to the ventromedial hypothalamus or preoptic area in ovariectomized, estrogen-primed rats - García-Juárez, Marcos; Luna-Hernández, Ailyn; Tapia-Hernández, Sandra; Montes-Narvaez, Omar; Domínguez-Ordoñez, Raymundo; Tecamachaltzi-Silvarán, Miriam B; Pfaus, James G; González-Flores, Oscar (Neuroscience letters, 2022)
In normal hormonal conditions, increased neuronal activity in the ventromedial hypothalamus (VMH) induces lordosis whereas activation of the preoptic area (POA) exerts an opposite effect. In the present work, we explored the effect of bilateral infusion of different doses of the apelin-13 (0.37, 0.75, 1.5, and 15 μg) in both brain areas on the expression of lordosis behavior. Lordosis quotient and lordosis reflex score were performed at 30, 120, and 240 min. Weak lordosis was observed following the 0.37 μg dose of apelin-13 at 30 min in the VMH of EB-primed rats; however, the rest of the doses induced significant lordosis relative to the control group. At 120 min, all doses induced lordosis behavior, while at 240 min, the highest dose of 15 μg did not induce significant differences. Interestingly, only the 0.75 μg infusion of apelin in the POA induced significant lordosis at 120 and 240 min. These results indicate that apelin-13 acts preferably in HVM and slightly in POA to initiate lordosis behavior in estrogen-primed rats.
Keywords: nucleus ventromedialis hypothalami; sexuální chování zvířat; estrogeny; Ventromedial Hypothalamic Nucleus; Estradiol; Intercellular Signaling Peptides and Proteins; progesteron; Apelin-13; lordóza; krysa rodu Rattus; Hypothalamus; Lordosis; Preoptic area; hypothalamus; mezibuněčné signální peptidy a proteiny; estradiol; Preoptic Area; Ventromedial hypothalamus; Estrogens; zvířata; Progesterone; area praeoptica; Rats; Animals; Sexual Behavior, Animal